Extent of Adaptability of Modern Agricultural Technologies by Rural Women at Samastipur District of Bihar - Arunima Kumari; Pooja Kumari (Indian Journal of Extension Education, 2016)
The prosperity and growth of a nation depends on the position and development of its females, as they not only constitute nearly half of its population but also positively influence the growth of remaining half of population. It is only women around whom the whole families growth rotates. The present study was conducted in samastipur district of Bihar with 100 respondents to find out the extent of adoption of improved technologies by rural women farmers. The study revealed that rural women were adopting post-harvest technologies more than the pre-harvest technologies and their adoption was affected by their knowledge level.